2007
DOI: 10.1111/j.1750-3841.2007.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation in Combination with Higher Storage Temperatures Maintains Chip‐Making Quality of Potato

Abstract: Freshly harvested and well-suberized potato (Solanum tuberosum) of varieties Kufri Jyoti, Lady Rosata, Kufri Laukar, and Hermises were processed by radiation at 78/149 Gy (D(min)/D(max)) dose and stored at 12 +/- 2 degrees C for 8 mo from March to October for assessment of chip-making quality. The firmness of the tubers in all the varieties processed remained unchanged during the period of storage. Chips of the desirable quality could be prepared from 7-mo stored Lady Rosata, Hermises, and Kufri Jyoti varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 17 publications
7
29
0
1
Order By: Relevance
“…KufriJyothi reported least tuber yield per plot (8.832 kg) and tuber yield per hectare (19.627 t/ha). The results are in agreement with other researchers who investigated that tuber yield varies significantly with variety, location and genotypes x environment interaction (Elfinesh, 2008, Gebreselassie et al, 2016, Pandey et al, 2004and Kumar et al, 2007 …”
Section: Yieldsupporting
confidence: 83%
“…KufriJyothi reported least tuber yield per plot (8.832 kg) and tuber yield per hectare (19.627 t/ha). The results are in agreement with other researchers who investigated that tuber yield varies significantly with variety, location and genotypes x environment interaction (Elfinesh, 2008, Gebreselassie et al, 2016, Pandey et al, 2004and Kumar et al, 2007 …”
Section: Yieldsupporting
confidence: 83%
“…Patel et al, (2008) and Kumar et al, (2007) also reported that maximum yield of small size tubers may be due to higher number of tubers as well as varietal character and adaptability or establishment effect of other growth attributes. Muthurajet al, (2005) reported that, the effect of heredity was significant with regard to tuber grades.…”
Section: Average Tuber Weightmentioning
confidence: 99%
“…Moisture content, water activity, and texture were determined as detailed earlier (Kumar, Khade, Dhokane, Behere, & Sharma, 2007;Kumar, Gautam, Powar, & Sharma, 2010).…”
Section: Analysis Of Physical Qualitiesmentioning
confidence: 99%
“…The organoleptic analysis was performed on a 9 point hedonic scale based on appearance, color, texture, aroma, and taste in a Taste Panel Laboratory in individually partitioned compartments (Kumar et al, 2007). The panelists (40 no.)…”
Section: Organoleptic Analysismentioning
confidence: 99%